Recenzja książki: Gargiliusz, Lekarstwa z owoców i warzyw, przełożyła Tatiana Krynicka, ISKŚIO UWr, Wrocław 2016, (Seria Biblioteka Antyczna), ss. 172 - Stuligrosz, Magdalena (Collectanea Philologica, 2018)
The first Polish translation of Gargilius Martialis’ treatise Medicinae de holeribus et pomis (Medicines from Fruits and Vegetables) was published in 2016 by Tatiana Krynicka. The translation is accompanied by a valuable commentary which provides the reader with rich information on botanical, medical and dietetic issues, and shows how the 3rd-century Roman author drawn on his literary sources and how he was referred to by late antique writers.